Visual entertainment construction in cooking content on Instagram: An analysis of themes and visual styles - Maharani Ayuning Tyas; Irfan Barro Bin Malik (Privietlab, 2026)
The rapid growth of cooking content on Instagram has transformed culinary activities into a form of visual entertainment, where visual communication plays a significant role in attracting audiences. This study aims to analyze how visual entertainment is constructed through visual themes and visual styles in Instagram cooking content. A qualitative approach was employed using Qualitative Visual Content Analysis (QVCA). The research analyzed 30 Instagram posts selected through purposive sampling from three cooking content creators: @bongnior, @onurwoodart, and @marinatayyebzadeh, each representing distinctive visual characteristics. Data were collected through non-participant observation and documentation, while analysis was conducted using a visual coding framework consisting of visual theme, visual style, visual narrative, and visual entertainment. The findings reveal that visual entertainment is constructed through the consistent integration of visual themes and visual styles. Bongnior emphasizes traditional cooking and togetherness through an authentic documentary style, Onurwoodart creates immersive outdoor cooking experiences by integrating natural landscapes into the cooking process, and Marinatayyebzadeh constructs visual entertainment through aesthetic food presentation and elegant visual compositions. Although all three accounts focus on cooking content, they employ different visual communication strategies to create distinctive viewing experiences. This study concludes that the consistency of visual themes and visual styles plays a crucial role in constructing visual entertainment and establishing the visual identity of cooking content on Instagram. These findings contribute to the development of visual communication studies by demonstrating how visual elements function as communication strategies in digital content.